Pengaruh Solvabilitas dan Profitabilitas Terhadap Kebijakan Dividen pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Jaris Shofia Abdulah; Andy Lesmana; Farizka Susandra (Jurnal Ilmiah Raflesia Akuntansi, 2026)
Dividend policy is an important financial decision that reflects a company's ability to balance the interests of shareholders and internal funding needs. The determination of dividend policy is influenced by various factors, including solvency and profitability, which represent the company's financial condition and performance. This study aims to analyze the effect of solvency and profitability on dividend policy in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This study employed a quantitative approach using secondary data obtained from the annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange. The population consisted of 37 companies in the food and beverage sub-sector. The sampling technique used was purposive sampling based on predetermined criteria, resulting in 12 companies with 48 observations during the study period. Solvency was measured using the Debt to Equity Ratio (DER), profitability was measured using Return on Assets (ROA), and dividend policy was measured using the Dividend Payout Ratio (DPR). Data analysis was conducted using multiple linear regression analysis with the assistance of EViews software. The results indicate that solvency does not have a significant effect on dividend policy. Meanwhile, profitability has a significant negative effect on dividend policy, indicating that companies with higher profitability tend to retain a larger portion of earnings for reinvestment rather than distributing them as dividends. Simultaneously, solvency and profitability have a significant effect on dividend policy. These findings suggest that dividend policy is determined by a combination of financial factors, particularly the company's ability to generate profits and manage its financial resources efficiently.